PROFIL KETERAMPILAN BELAJAR MAHASISWA BIMBINGAN DAN KONSELING YANG MENGIKUTI ORGANISASI KEMAHASISWAAN DI STKIP PGRI SUMATERA BARAT - Yuliandri, Deni; KASIH, FITRIA; Nita, Rahma Wira (Bimbingan dan Konseling, 2014)
Based on the phenomena in the field that follows the guidance and counseling students not skilled in the learning organization. Guidance and counseling still concerned because the students other than the activities of the lectures. Target of this research: An Analysis a the profile of skill learn student guidance and counseling following students organization in some part, such as: 1) Remember learning material. 2) Concentration follow learning. 3) Manage or exploit time. This research is descriptive. Population in this research is total 41 people. Technique sampling in this research use saturated sampling technique that all population is sample. The result of students research skills profile guidance and counseling, in generally criterion is enough. Result of research base on sub-variable which: 1) Remember learning material is dificient. 2) Concentration follow learning is enough. 3) Manage or exploit time is enough. Based on the research results of student guidance and counseling should be able to remember the lecture material that has been studied, by repeating material that has been discussed, so that students learn the have good results.